Preparation and adsorption properties of magnetic hydrophobic cellulose aerogels based on refined fibers. (15th May 2021) - He, Xinghua; Chen, Tiantian; Jiang, Tianyan; Wang, Cong; Luan, Yunhao; Liu, Pengtao; Liu, Zhong
Highlights: The preparation of aerogels was based on refined fibers. The magnetic hydrophobic aerogel was made by using MTES and Fe3 O4 nanoparticles. The aerogel had high adsorption capacity(181 g/g) and good reusability. Abstract: A novel approach was introduced to prepare very low density, highly porous, economic, reusable, hydrophobic, and magnetic cellulose aerogels from hardwood dissolving pulp via a simple freeze-drying procedure. The aerogels showed outstanding adsorption efficiency for several oils and organic solvents and demonstrated excellent selectivity for absorbing oil from an oil/water mixture. Moreover, they were easily collected by an external magnet, indicating excellent recyclability and reusable for at least 10 cycles while still retaining supreme adsorption capacity (up to 181 g/g for silicone oil). This study proposes an economic and novel method for the large-scale preparation of hydrophobic and magnetic cellulose aerogels, making them a promising candidate for the efficient and sustainable cleaning of oils and chemical spills.